Cultural Imprints on Urban Housing: A Spatial Analysis of Apartment Designs in Kenya, Ghana, and South Africa - Jung Yun Choi; Jaepil Choi (Buildings)
Apartment design is often assumed to follow a standardized model, disregarding cultural influences. However, cultural context can significantly shape the spatial organization of living environments. A significant gap exists in addressing how cultural factors influence apartment design in rapidly urbanizing African cities. Modern architectural practices frequently overlook the sociocultural dynamics essential for creating living spaces that resonate with local populations. This study investigates the spatial configuration of apartment units in three African countries—Kenya, South Africa, and Ghana—challenging the notion of universally homogeneous apartment designs. By applying Space Syntax, a quantitative analysis tool, this study examines how cultural factors distinctly influence the layout of apartments. The findings reveal significant variations, particularly in the design of corridors, domestic servant quarters, and the separation of private zones. This research highlights the importance of incorporating cultural considerations into architectural design processes to promote housing solutions that are functionally efficient, culturally relevant, and responsive to local social norms. Future research could explore how these cultural influences manifest across different housing types, such as informal settlements and high-rise apartments, or examine the impact of migration and globalization on evolving housing needs.